Inequality and growth in the twenty‐first century. (14th September 2021) - Luo, Weijie
Abstract: This paper analyzes how economic growth can be caused by changes in the income distribution. Persson and Tabellini (1994, The American Economic Review, 84, 600‐621) argue that productivity‐induced income inequality leads to lower growth since distortionary taxes increase and harm capital accumulation. However, this prediction is often challenged empirically. This paper distinguishes between capital income inequality and inequality induced by differences in labor productivity. Greater capital income inequality leads to lower labor tax rates, leading to higher growth. Using data for OECD countries, subsequent growth is found to be positively related to capital income inequality, and negatively related to labor income inequality, as originally conjectured.